Construction of Escherichia coli BL21/A-53 producing histidine-tagged carboxymethylcellulase and comparison of its characteristics with CMCase without histidine-tag. Issue 2 (7th February 2019) - Kang, Duk-Un; Lee, Yong-Suk; Lee, Jin-Woo
Abstract: To enhance recovery yield of carboxymethylcellulase (CMCase), E. coli BL21/A-53 producing the histidine-tagged CMCase was constructed in this study. The recovery yield of the histidine-tagged CMCase using the His-tag affinity chromatography was 39.8%. The predicted molecular weight of the histidine-tagged CMCase was determined as 56, 260 Da. Its K m and V max were 9.3 g l −1 and 76.3 g l −1 ·min −1, respectively. The histidine-tagged CMCase hydrolyzed avicel, carboxymethylcellulose (CMC), filter paper, pullulan, xylan, but there was no detectable activity on cellobiose, p -Nitrophenyl-β-D-glucopyranoside ( p NPG). The optimal temperature and pH for the enzymatic reaction of the histidine-tagged CMCase was 50 °C and 5.0. The histidine-tagged CMCase was enhanced by CoCl2 until the concentration of 100 mM, but inhibited by EDTA, HgCl2, MnCl2, NiCl2, and RbCl2 . The characteristics of the histidine-tagged CMCase produced by E. coli BL21/A-53 were compared with those of CMCase without the histidine-tag of Bacillus subtilis subsp. subtilis A-53. The little changed characteristics of the histidine-tagged CMCase compared to the CMCase without a His-tag seemed to be the conformational change in the structure due to a His-tag.